Forest Management in the Interface: Forest Cooperatives - Sarah F. Ashton; Bruce Hull; Rien M. Visser; Martha C. Monroe (EDIS, 2008)
Revised! FOR-176, a 7-page illustrated fact sheet by Sarah F. Ashton, Bruce Hull, Rien M. Visser, and Martha C. Monroe, describes this bottom-up, voluntary approach to implementing coordinated ecosystem management among multiple owners of fragmenting interface forestland — types of cooperatives, benefits, costs and reservations, funding. Includes suggested reading and references. Published by the UF School of Forest Resources and Conservation, August 2008.